Diagnosis of silent pheochromocytoma and paraganglioma. Issue 1 (January 2013) - Clifton-Bligh, Roderick
Pheochromocytomas or functioning paragangliomas can present in a dramatic manner with headache, palpitations and sometimes shock, but many occur with few symptoms despite at times markedly elevated catecholamine levels. Hypertension is not invariable, and may be paroxysmal. Increased diligence in the diagnosis of presymptomatic pheochromocytoma/paraganglioma is warranted from autopsy studies, suggesting that many of these tumors may be fatal at first presentation. Fortunately, an increasing number of pheochromocytomas/paragangliomas are now diagnosed before the advent of symptoms, either as an incidental finding on abdominal imaging or by targeted surveillance in subjects with known genetic susceptibility. The challenges and pitfalls associated with diagnosis of these silent pheochromocytoma/paragangliomas are reviewed in this article.